Modeling, dynamics, optimization and bioeconomics II : DGS III, Porto, Portugal, February 2014, and Bioeconomy VII, Berkeley, USA, March 2014 – selected contributions /: DGS III, Porto, Portugal, February 2014, and Bioeconomy VII, Berkeley, USA, March 2014 – selected contributions. (2017) - Unknown
No abstract available